PENERAPAN SAK-EMKM DALAM PENYUSUNAN LAPORAN KEUANGAN PADA PABRIK TAHU ZR DESA HELVETIA - Munte, Mei Hotma Mariati; Zega, Nicolaus Sebastian (LPPM Universitas Bina Bangsa, 2023)
This research aims to prepare financial statements based on the Small and Medium-sized Entity Financial Accounting Standards (SAK EMKM) at ZR Tofu Factory. The research method used is quantitative descriptive. The obtained information consists of income and expense records available at ZR Tofu Factory that have been compiled. The research results show that the process of preparing financial statements with SAK EMKM at ZR Tofu Factory involves several stages, including data collection, journalizing, posting to the general ledger, preparing the pre-adjustment trial balance, making adjusting entries, preparing the post-adjustment trial balance, calculating the cost of goods manufactured, and preparing financial statements according to the format and requirements of SAK EMKM. This research contributes to the understanding of the process of preparing financial statements using SAK EMKM at ZR Tofu Factory. The implications of this research highlight the importance of improving the understanding and knowledge of SAK EMKM for the owners of ZR Tofu Factory and the need to consistently and diligently record all income and expenses, which can greatly assist in future financial statement preparation